Recurrent breeding method enhances the level of blackspot (Didymella pinodes (Berk. & Blox.) Vestergr.) resistance in field pea (Pisum sativum L.) in southern Australia. Issue 4 (18th March 2014) - Adhikari, Kedar N.; Khan, Tanveer N.; Stefanova, Katia; Pritchard, Ian; Link, W.
Abstract Blackspot, caused by Didymella pinodes (Berk. & Blox.)Vestergr., is one of the most important diseases of field pea, causing significant reduction in seed yield and quality in southern Australia and in other parts of the world. Development of resistant germplasm has been slow because of the low level of resistance found in the available germplasm, poor reliability of screening methods and the polygenic nature of inheritance. Crosses were made between agronomically suitable lines and resistant germplasm from different sources. Their progeny were advanced through the single seed descent method and single plants were selected at F4/F5. The F4/F5 derived lines were screened against blackspot in the field under disease pressure and evaluated for grain yield at multilocations over 2 years. Despite the low level of resistance in the parental germplasm, the level of resistance has increased significantly in the new germplasm. Many of the resistant lines were late and low yielding, but lines with higher resistance and early flowering and high yield potential were also identified indicating that the disease resistance, adaptation and yield potential can be combined. However, the resistance identified in this study is only partial and suitable agronomic practices may need to be supplemented to minimise the yield loss and enhance the benefits of this partial resistance.